"Control interno en el complejo recreacional turístico Somagg del cantón La Mana periodo 2012" - Manzo Arreaga, Andrea Roxanna (2014)
Today the business growth and competition between them have increased their activities, objectives, and the resources they use, they are used correctly and efficiently, seeing the need for effective internal control. This project documents the implementation of an internal control system for recreational Somagg Complex in Canton La Maná. Sommag is a private company based in the city of La Manna, dedicated to providing tourism services. The study applied a SWOT (strengths, weaknesses, opportunities and threats), in search of internal and external factors that contribute to the identification, formulation and implementation of key controls to strengthen its control environment. Organizational chart is also structured to delineate responsibilities for each area, identifying the core of the operation of Somagg. Through the implementation of this internal control Somagg company was able to identify weaknesses and strengths in each of their areas, being very efficient in managing human resources with control of 90 %, but is very inefficient in controlling fixed assets (51%) and inventory management (52 %), with these two high risk areas of control, 18 and 49 % respectively, which at no time be corrected can trigger financial problems and accountings.